Avaliação do potencial de contaminação de águas subterrâneas por agrotóxicos no planalto da Ibiapaba - CE - Pedroza, Vanêssa Gomes (2024)
Industrial agriculture, through monocultures, strong mechanization and technology, encourages agricultural practices dependent on large volumes of pesticides. It has also contributed to large loads of pollutants in the water. Globally, agriculture is among the main causes of water pollution and is responsible for the discharge of large quantities of pesticides. In the world, most of the water used is underground, and it has also been suffering from the impacts of pollutants such as pesticides. The degradation of water quality has impacts on biodiversity, people and their health. Brazil is the largest consumer of pesticides in the world. Thus, one way of predicting risks can be through pesticide leaching prediction models, as they can provide an understanding of problems by identifying relationships (cause and effect), predictions and give future suggestions. The general objective of this research was to estimate the potential risk of pollution of groundwater in the Ibiapaba Plateau caused by the active ingredients (a.i.) of pesticides most used in São Benedito. This study modeled two groundwater leaching potential scenarios for 35 pesticide active ingredients, using their respective physicochemical properties, applied to the Groundwater Ubiquity Score (GUS) and LEACH. The results obtained were that five active ingredients (iprodione, methomyl, boscalid, azoxystrobin, dimethoate) can be considered in the transition zone and three (thiophanate-methyl, thiamethoxam and chlorantraniliprole) can be considered in the leaching zone. It was also concluded that there may be risk vulnerability to contamination by pesticides in the Ibiapaba region, especially in regions that have Dystrophic Red Oxisols and Quartzarene Neosols, as in these types of soils, and considering the slope of the land, the potential for infiltration of contaminant can be medium to high. As water is part of sustainable development concerns, there needs to be a ban or progressive reduction in the use of pesticides in the region, as well as measurement or verification of water quality and quantity parameters in Ibiapaba, on a continuous or periodic basis. Human health and well-being, as well as the aquatic ecological balance, must not be affected by deterioration in water quality.